The Roles of Social Media Content Quality on Street Food Consumers - Wilujeng, Ita Prihatining; Wardhana, Ery Tri; Murwani, Danardana; Handayati, Puji; Latif, Sahraman D. Hadji (Universitas Negeri Malang, 2024)
Online reviews continue fostering a renewed word-of-mouth spread in the food and beverage industry. Consumers increasingly use online reviews to inform them about food and beverage products. Therefore, it is critical to enhance comprehend of the behavioral consequences of e-WOM. This study examines the role of heavy/light social media user in the relationship between e-WOM on social media platforms, attitude toward information, and information usefulness. We adopt the conceptual model to identify what influences consumers to adopt information from online reviews in their decision-making. A self-administered questionnaire was used to collect data from 300 respondents. Data analysis has been conducted using PLS-SEM, which measures the influence of e-WOM, attitude, and subjective norms on information usefulness and purchase intention. The results of this study reveal that e-WOM, attitude, subjective norm, and information usefulness are strong predictors of consumers' purchase intention. These outcomes suggest that high-involvement consumers adopt online review information when they make decisions about making purchases. Keywords: E-WOM, Information usefulness, Attitude towards information, Subjective norm, Purchase intention